Integration of HR Culture in Four Role Model for Smart Campus - Anggoro, Sigit (Pandawan Incorporation, Alphabet Incubator Universitas Raharja, 2026)
Digital transformation in higher education is often constrained by the readiness of human resources. This study aims to analyze how military based organizational cultural values, namely discipline, loyalty, and courtesy strengthen the implementation of Dave Ulrich Four Roles of Human Resource model in supporting the transformation toward a Smart Military University. Using a qualitative case study approach at Jenderal Achmad Yani University, data were collected through in depth interviews observations and document analysis. The analysis visualized through a concept map shows that the interaction between the value of discipline and the Administrative Expert role has the highest frequency of references predominantly expressed by respondents from the ICT team and the administrative bureau. These findings indicate that data integrity within digital systems is highly dependent on compliance with established procedures. Meanwhile the value of loyalty emphasized by university leadership serves as the foundation of the Strategic Partner role in executing the institutional vision while courtesy underpins the Employee Champion role in delivering services. This study demonstrates that local cultural values constitute a determining variable for the successful performance of human resource management functions in the digital era.